Implementasi Kebijakan Penataan Pedagang Kaki Lima (Pkl) Di Kota Kendari Provinsi Sulawesi Tenggara - Haeruddin Haeruddin (Jurnal Administrasi Publik dan Pembanguan, 2019)
The existence of street vendors (PKL) becomes the most urgent and empirical problem to be handled seriously for the local government to find a solution immediately. Contemporary phenomenon, frequent eviction of the existence of street vendors (PKL) demands the local government to find a place or alternative location for street vendors (PKL) in running their business.This study aims to determine the implementation of policies and factors that influence the policy of structuring street vendors (PKL) in Kendari City. This research uses qualitative descriptive method with informant determination technique by purposive sampling. While the collection technique, through; observation, interviews and documentation.The results of the study showed that the implementation of street vendors (PKL) structuring policy in Kendari City had been going well enough, while the influential factors were the lack of policy socialization, levies levied on street vendors (PKL), so that the difficulty was put in order.